2013
DOI: 10.1606/1044-3894.4288
|View full text |Cite
|
Sign up to set email alerts
|

African American Adolescents' Interactions with Their Substance-Using Mothers

Abstract: Understanding the interactions that African American youth have with their substance-using mothers is important because of the increased likelihood that these youth depend on their mothers as their primary providers. In-depth interviews were conducted with 14 urban-dwelling, African American adolescents with substance-using mothers to explore the nature of their interactions. Youth report maternal influence on their attitudes in general and toward child-rearing and peer group affiliations. Communication betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Ten studies (11 papers) reported that all young people were living with the parent who uses substances at the time of data collection (Ahuja et al, 2003; D’Costa & Lavalekar, 2021; Dundas, 2000; M. Hill et al, 1996; Johnson, 2013; Mudau, 2018; Ramírez Dávila et al, 2014; Reupert et al, 2012; Templeton et al, 2009; Tinnfält et al, 2018; Velleman et al, 2008). All other studies reported varied living arrangements for young people.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies (11 papers) reported that all young people were living with the parent who uses substances at the time of data collection (Ahuja et al, 2003; D’Costa & Lavalekar, 2021; Dundas, 2000; M. Hill et al, 1996; Johnson, 2013; Mudau, 2018; Ramírez Dávila et al, 2014; Reupert et al, 2012; Templeton et al, 2009; Tinnfält et al, 2018; Velleman et al, 2008). All other studies reported varied living arrangements for young people.…”
Section: Resultsmentioning
confidence: 99%
“…A minority voice within some studies included children and young people who reflected that their relationship with a parent who uses substances was not affected (Alexanderson & Näsman, 2017; Bancroft et al, 2004; Bernays & Houmøller, 2011; Fraser et al, 2009; M. Hill et al, 1996; Johnson, 2013; McGuire, 2002; Moore et al, 2011; Reupert et al, 2012; Silva et al, 2013; Tinnfält et al, 2018; Wilson et al, 2012), or even that they enjoyed the affection and generosity from their parents when they had been drinking alcohol (M. Hill et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have commented on the criticality of the family system and ecology in which parentification takes place. For example, Johnson (2013) and Burton (2007) contended that in the assessment and treatment of families where parentification exists, determining the extent to which social support and extended family members are available to assist the parentified family member is paramount. In Black American families, kinships and kin may buffer or exacerbate the negative outcomes associated with parentification (Johnson, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Johnson (2013) and Burton (2007) contended that in the assessment and treatment of families where parentification exists, determining the extent to which social support and extended family members are available to assist the parentified family member is paramount. In Black American families, kinships and kin may buffer or exacerbate the negative outcomes associated with parentification (Johnson, 2013). In her description of the importance of kinships and fictive kin, Hall (2013) asserted “the clinician should routinely evaluate how the social support system impacts treatment either negatively or positively” (p. 491).…”
Section: Literature Reviewmentioning
confidence: 99%